Pressupostos de avaliação da aprendizagem na aplicação de jogos digitais voltados para o ensino de Química: uma análise a partir da revisão sistemática da literatura - PACHECO, Alan Carlos Rocha (2022)
In the search for new learning tools, digital games have increasingly shown their potential, being used by students of various levels of education around the world. Despite this, some doubts hover over educators who intend to use or already use this technology in their classes, such as how to assess learning based on digital games. Assessment is an important part of the teaching and learning process and, in this case, it serves both to know if there have been advances in student learning, as well as to analyze the contributions of the use of games in the context of the classroom. Thus, this work aims to investigate how the process of evaluating learning based on the use of digital games in chemistry teaching is being conducted, based on the analysis of academic production published in electronic databases. For this, data collection took place through a Systematic Literature Review, developed to provide information and identify relevant studies published between 2011 and 2021 in the SCOPUS, Web of Science, ACS Publications and CAPES Periodicals Portal. The analysis of the articles collected was carried out from the perspective of content analysis, through the coding and categorization of the analyzed data. As a reference for analysis, works by authors who deal with evaluation, such as Luckesi and others who deal with games such as Whitton, Michel and Chen, were used. The review process resulted in 49 articles selected as the object of research, as they are relevant to the study. The results pointed to an increasing use of digital games in the teaching of chemistry, highlighting their potential as an effective learning tool, in addition to their versatility in being able to be adapted to various contents and different levels of education. As for the assessment of learning, there was a greater frequency of works that sought to evaluate issues related to the functioning of the game and left out questions about the evaluation that could attest if there was any learning during the digital game.